Spring Contact Model of Tape Peeling: A Combination of the Peel-Zone Approach and the Kendall Approach - Li, Yuanzhe; Pesika, Noshir S.; Zhou, Ming; Tian, Yu (Frontiers in Mechanical Engineering, 2018)
Energy-based and force-based approaches are two basic ways to establish an adhesion model. For the adhesion of tape-like thin films, the Kendall equation considers the overall energy balance but inherently contains little information of the peel zone geometry and stress distribution. The peel zone model provides an empirical approximate of the peel front from the approach of a force description and coincides well with experimental results for a wide range of peel angles. However, the peel-zone model itself has not been unified with the Kendall equation yet. We propose a two-layer spring contact tape peeling model which considers the balance between the stretching force of the backing layer and the adhesive force transferred through the adhesive layer. The model provides an analytic shape description of the curved bifurcation region of the peel front. An approximate analytic solution of the peel force reduces to the Kendall equation by considering a Kendall-like energy conservation critical criterion, which further supports the proposed model. Further analysis of the relationship between the length of the peel zone and the adhesive force provides insight into the validity of the peel zone model. The proposed model provides a new insight in the tape peeling process and mathematically builds a potential bridge between the Kendall model and the peel-zone model.